Red Sea Bream Iridovirus Stability in Freeze–Thaw Cycles: Quantitative Assays of Infectious Particles - Ji-Min Jeong; Gyoungsik Kang; Jae-Ok Kim; Jeong-Tae Lee; Chan-Il Park; Kyung-Ho Kim (Animals, 2025)
Red sea bream iridovirus is a serious threat to farmed fish, but little is known about how repeated freezing and thawing affect its stability. This study investigated the effects of repeated freeze–thaw cycles on RSIV infectivity by comparing quantitative polymerase chain reaction (qPCR), viability qPCR (vqPCR), and 50% tissue culture infectious dose (TCID50) assays. While qPCR detected high amounts of viral DNA after multiple cycles, both viability qPCR and TCID50 revealed a significant loss of infectivity unless serum was present. Correlation analysis showed a high degree of agreement between vqPCR and TCID50, indicating their high compatibility for assessing viral infectivity. However, the correlations between qPCR and vqPCR, as well as between qPCR and TCID50, were significantly lower, suggesting that qPCR alone may overestimate viral infectivity by detecting non-infectious viral DNA. These results demonstrate the critical role of serum in preserving RSIV infectivity and highlight the superior accuracy of vqPCR and TCID50 in assessing viral infectivity compared with qPCR. This study emphasizes the importance of serum in storage media and suggests that combining vqPCR with TCID50 is a more reliable measure of RSIV infectivity than qPCR alone.